A phytosociological study of aquilaria malaccensis lamk. and its communities at Sungai Udang forest reserve, Malacca / Sarah Abd. Razak - Sarah, Abd. Razak (2016)
A phytosociological study was done to assess the composition of Aquilaria malaccensis Lamk. and the ecological relationship between the species within the communities. Braun-Blanquet (1964) method was adopted in the present study. A total of 1668 individual trees with diameter at breast height (DBH) of 5 cm and above were found in the 25 plots in Sungai Udang Forest Reserve, Malacca, Peninsular Malaysia of which overall floristic composition consisted of 85 species belonging to 79 genera and 38 families. The most abundant family is the Euphorbiaceae with 224 individual trees, followed by Myrtaceae and Anacardiaceae representing 212 and 197 individuals, respectively. The phytosociological study identified a community which was Aquilaria malaccensis - Artocarpus rigidus community with two sub-communities known as Palaquium gutta sub-community and Barringtonia racemosa sub-community. Based on the calculated Importance Value Index (IVi), Spondias cytherea (Anacardiaceae) was the most important species in the study area with an importance value index (IVi) of 23.9%. The second most important species in the study area was Syzygium sp. (Myrtaceae) with an importance value index (IVi) of 22.8%, followed by Elateriospermum tapos (Euphorbiaceae) and Aquilaria malaccensis (Thymelaeaceae) with an importance value index (IVi) of 17.2% and 13.0%, respectively. As for species diversity, the Shannon-Weiner Diversity Index (H’) for the whole 25 plots of the study area (Aquilaria malaccensis-Artocarpus rigidus community) showed an index value of 3.67, while the Simpson’s index of diversity (1-D) for the whole 25 plots (Aquilaria malaccensis-Artocarpus rigidus community) showed an index value of 0.96. The H’ values and D values proved that the study plots are considered as obtaining a fairly high species diversity in comparison with many studies conducted at the tropical rainforests in Peninsular Malaysia. The floristic composition in the family level obtained in this study with Euphorbiaceae as the dominant family is quite similar to those found in other tropical forests in Peninsular Malaysia. The fairly high species diversity and the good soil characteristics obtained from the study area shows that Aquilaria malaccensis Lamk. and its communities can successfully interact socially between each other and able to live healthily together in an ecosystem. The soil in the study area was acidic and dominated by clay loam which shows that the soil is suitable for the provision of nutrients to the plants. This study also concluded that high soil fertility promotes the high species diversity and richness of an area. The correlation analysis between the physico-chemical characteristics of soil at all the 25 plots in the Sungai Udang Forest Reserve concluded that the correlation between the chemical content of soil in this study was moderate. Furthermore, the Pearson’s correlation analysis determined that the vegetation diversity or plant communities were significantly and positively correlated with soil parameters, particularly soil pH, CEC, available K, available P, available C and available N. Therefore, the soil characteristics of an environment should be an important criterion for species distribution. The composition and distribution of species in this study might be also influenced by other environmental factors such as natural forest gap, altitude and topography. The new information on Aquilaria malaccensis Lamk.and its communities obtained from this study could contribute to the future plantation work, by using all the exact species existed in the discovered new communities as a reference in planting trees.